How does live streaming affect tourists’ intention — a psychology theory perspective - Naipeng Bu; Ying Li; Yanan Li; Kangping Wang; Deyan Zhao; Xingwang Jiao; Tianruo Li (Scientific Reports)
Abstract As a novel experiential approach, live streaming at tourist destinations has garnered significant attention and profoundly impacts tourists’ travel decisions. This study aims to validate the effects of usefulness, authenticity, and interactivity of destination live streams on the decision-making process of tourists. Grounded in stimulus–organism–response (S-O-R) theory, this research identifies the usefulness, authenticity, and interactivity of destination live streams as the “stimulus,” while telepresence and trust as the “organism,” with tourists’ travel decisions as the “response.” Utilizing survey questionnaires, 274 valid data were collected and analyzed through structural equation modeling in SPSS 26.0 and Amos 28.0 software to assess the impact of destination live streams on tourists’ travel decisions. The findings reveal that both interactivity and authenticity positively influence tourists’ telepresence. Additionally, the usefulness, interactivity, and authenticity of these live streams also positively affect perceived trust among viewers, which subsequently enhances their travel decisions. This study highlights the usefulness, authenticity, and interactivity as external stimuli in destination live streams, elucidating their influence on tourists’ travel decisions and contributing to the understanding of the live streaming phenomenon within the tourism sector.